Pristojnost nadzora državnega nadzornega organa nad delovanjem sodnih organov - Žitnik, Nina (Podjetje in delo, 2022)
As the world becomes ever more digital, courts and other public authorities must take care not to infringe on the individual's right to the protection of personal data when publishing their decisions, as this right is becoming increasingly important in the age of information technology. The right to data protection is closely linked to the right to privacy, and therefore the actions of the courts and public authorities must be correct, lawful, clear and precise, while at the same time providing for the protection of that right in the event of its violation, both at the national and international level. As part of the binding rules, judicial protection and effective remedies must be available to the individual whenever a violation of a right occurs, which is why it is necessary to ask the following: (1) How and on what basis do courts process individuals' personal data? (2) When do courts act as judicial authorities? (3) Are courts, as a so-called public sector, subject to Information Commissioner's oversight in terms of institutional protection? (4) If the Information Commissioner does not have the power to supervise the work of the courts under the provisions of Article 55(3) of the Regulation, how can an individual enforce their rights? In this article, we will answer these questions in the light of (also comparative) case law and legal literature.
Keywords: EU law; judicial protection; nacionalni nadzorni organi; nacionalno pravo; national law; national supervisory authority; pravna sredstva; pravo EU; remedies; right to protection of personal data; sodno varstvo; varstvo osebnih podatkov